EFEKTIVITAS MASSAGE EFFLEURAGE TERHADAP PENURUNAN NYERI HAID: Array - Kiki Natassia (Yayasan Citra Dharma Cindekia, 2022)
Menstrual pain or dysmenorrhea is pain during menstruation before or during menstruation. The incidence of dysmenorrhea in the world is very large. On average, more than 50% of women worldwide experience dysmenorrhea. The impact that occurs if dysmenorrhea is not treated can be a pathological condition (abnormality or disorder) that can or trigger an increase in mortality, including infertility. An easy treatment for dysmenorrhea is massage effleurage. The method of massage or massage on the abdomen with the effleurage technique is a form of skin stimulation that is used during the menstrual process to reduce pain effectively. The purpose of this study was to determine the effectiveness of effleurage massage on reducing menstrual pain. The type of research used is a quasi-experimental with a quantitative approach. The sampling technique used was consecutive sampling with a total of 30 respondents consisting of 15 respondents from the treatment group who were given effleurage massage, and 15 respondents who were the control group. The results of the study in the intervention group before the effleurage massage was done the average pain scale was 5.00 and after it was done 2.33. In the control group the average pain scale was 5.27 and after it was done it was 5.13. The results of the bivariate test in the group of respondents who were given effleurage massage after the Wilcoxon signed ranks test showed p value = 0.000 <0.05, which means that effleurage massage is effective in reducing menstrual pain.